IMPLEMENTASI PROGRAM DANA BANTUAN OPERASIONAL SEKOLAH SMA NEGERI 1 PASANGKAYU KABUPATEN MAMUJU UTARA - Anas, Aswar (Katalogis, 2016)
This research aims at knowing and analyzing the implementation of School Operational Assistance Fund at SMAN 1 Pasangkayu of North Mamuju regency. The method used is qualitative, and the informants of the research were determined purposively to who are deemed to understand the problems investigated. The informants are the Head of Education, Culture, Youth and Sports of North Mamuju regency, Head of Section of Secondary Education, the School Committee, studentsâ€™ parents who received the assistance funds, Principal of SMA 1 Pasangkayu. Type of data used are primary data and secondary data. Data collection was done through observation, interview, and documentation. The results shows that communication is one of the main factors in policy implementation, communication becomes a major pathway for the implementation of each program. Human resources are the main factors that should be possessed by any particular institution or unit both government and non government institutions. Vice versa if the perspectives of the implementers are different from the decision makers, the implementation process of a policy becomes increasingly difficult. And in such cases, implementers will use the flexibility and sometimes in subtle ways inhibit, or will benefit each individual in the process of policy implementation.Â